Do I make myself clear? Why writing well matters - Evans, Harold (London, 2017)
"Harry Evans has edited everything from the urgent files of battlefield reporters to the complex thought processes of Henry Kissinger, and he has been knighted for his services to journalism. In Do I Make Myself Clear?,his definitive guide to writing well, Evans brings his indispensable insight to the art of clear communication. The right words are oxygen to our ideas, but the digital era, with all of its TTYL, LMK and WTF, has been cutting off that oxygen flow. The compulsion to be precise has vanished from our culture, and in writing of all kinds we see a trend towards more - more speed and more information, but far less clarity. Evans provides practical examples of how editing and rewriting can make for better communication, even in the digital age. DO I MAKE MYSELF CLEAR? is an essential text, and one that will provide every reader an editor at their shoulder."